2007
DOI: 10.1016/j.clim.2007.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Toward the development of multi-epitope p53 cancer vaccines: An in vitro assessment of CD8+ T cell responses to HLA class I-restricted wild-type sequence p53 peptides

Abstract: Wild-type sequence (wt) p53 peptides are attractive candidates for broadly applicable cancer vaccines. Six HLA-A2 or HLA-A24-restricted wt p53 peptides were evaluated for their ex vivo immunogenicity and their potential for use in cancer vaccines. Peripheral blood mononuclear cells (PBMC) obtained from HLA-A*0201 + and/or HLA-A*2402 + normal donors and subjects with squamous cell carcinoma of the head and neck (SCCHN) were analyzed for p53 peptide-specific reactivity in ELISPOT IFNγ assays. CD8 + T cells in 7/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…Currently a variety of p53-based vaccines have proved effective in animal models and are now undergoing trial in man. Key p53 peptide epitopes have been discovered (Hoffmann et al 2002;Sakakura et al 2007) and the major problem has emerged as one of steering the T-cell response toward effective tumor rejection rather than tolerance. In this context it is provocative to think about how drugs that modulate p53 processing may enhance or inhibit such T-cell responses.…”
Section: P53 Vaccinesmentioning
confidence: 99%
“…Currently a variety of p53-based vaccines have proved effective in animal models and are now undergoing trial in man. Key p53 peptide epitopes have been discovered (Hoffmann et al 2002;Sakakura et al 2007) and the major problem has emerged as one of steering the T-cell response toward effective tumor rejection rather than tolerance. In this context it is provocative to think about how drugs that modulate p53 processing may enhance or inhibit such T-cell responses.…”
Section: P53 Vaccinesmentioning
confidence: 99%
“…Our previous study showed that CD8+ T cell precursors responsive to wt p53 epitopes were detected in the circulation of most subjects with early disease relative to subjects with advanced disease who were largely in the non-responder category [18]. Interestingly, in patients with a tumor burden, our data indicated that patients with early disease showed either Th1-polarized or mixed Th1/Th2 responses, while those with advanced disease had either Th2-polarized or Th1/Th2 responses.…”
Section: Discussionmentioning
confidence: 63%
“…Ovarian cancer often expresses a mutant form of p53 early in its development making it a potential target for immunotherapy [27]. Early preclinical studies showed that immune responses could be generated to p53 [28]. These data coupled with evidence of possible improved OS in patients who develop antibodies to p53 naturally make it a target of interest [29].…”
Section: Active Immunotherapymentioning
confidence: 99%